PENGARUH PEMASARAN INTERNAL TERHADAP KEPUASAN KERJA DAN ORIENTASI KONSUMEN DI RSUD PATUT PATUH PATJU LOMBOK BARAT - Ni Made Citra Resmi (JMM UNRAM - MASTER OF MANAGEMENT JOURNAL, 2016)
The research was conducted to analyse (1) The signification impact from internal marketingto job satisfaction at Region General Hospital Patut Patuh Patju West Lombok. (2) The significationimpact from job satisfaction to customer orientation at Region General Hospital Patut Patuh PatjuWest Lombok. (3) The signification impact from internal marketing to customer orientation at RegionGeneral Hospital Patut Patuh Patju West Lombok. This research is an assosiatif causal study. Thedata were collected by using questionaires distributed to nurses in Region General Hospital PatutPatuh Patju West Lombok totaling 150 people. The data was processed and analysed by Path Analysisthrough AMOS software. The results showed that: (1) Internal marketing has a positive andsignificant impact on job satisfaction. (2) Job satisfaction has a positive and significant impact oncustomer orientation. (3) Internal marketing has a positive and significant impact on customerorientation. (4) Internal marketing affects customer  orientation indirectly  through job satisfaction. Keywords: Internal Marketing, Job Satisfaction, Customer Orientation